The implementation of the Common Assessment Framework in the assessment of administrative and efficiency of nursing service in General Hospital of island region. - Apostolos Efkarpidis (Ene, 2017)
Introduction: The Common Assessment Framework (CAF) is an easy to use tool of Total Quality Management (TQM) which is available to the public sector organizations in Europe. The Common Assessment Framework applied every two years providing a self-assessment framework to organizations, conceptually similar with the European Foundation Quality Management, taking into account their differences. It is common for all public organizations ensuring the comparability of results between similar services. Objective: To measure the existing administrative and operational level of Nursing Service in General Hospital. Methodology: The study was authorized by the General Manager of the Hospital. We followed the steps of the procedure provided the Implementation Guide of the CAF and used the questionnaire of the Guide. The sample consisted of 32 employees (Self-Assessment Group) of all categories in a total of 101 employees. The analysis was performed with the Excel program. Results: The results of the evaluation were initiated between two rating scales based on the average (50 points) a) of the scale with grades from 31 to 50 (below average) indicating the relative satisfaction for some activity and the moderate level of efficiency and effectiveness, and b) of the scale with grades from 51 to 70 (above average) indicating satisfaction for some activity and the good level of efficiency and effectiveness. The rating on the nine criteria of the CAF were: 1) Leadership (57.36), 2) Strategy - Planning (44.1), 3) Human Resource Management (50.07), 4) Partnerships - Resources (41,18), 5) Process Management - Changes (30.04), 6) Results for the Citizen (49.17), 7) Results for the Human Resources (42.13), 8) Results in Society (53, 97), 9) Main results (53,78). Conclusions: Τhe Nursing Service of the General Hospital was evaluated for its administration as well as the organizational performance by staff and citizens, based on the CAF. Seventy two weak points were spoted needing improvement, and the strengths to be retained.